Evaluasi Kesesuaian Lahan Pasang Surut untuk Tanaman Lada (Piper nigrum Linn.) di Desa Galing Kecamatan Galing Kabupaten Sambas - Suriadi, Suriadi; Hazriani, Rini; Gunawan, Joni (Fakultas Pertanian Universitas Tanjungpura, 2023)
Land evaluation is an approach for assessing the potential of land resources. Results of the evaluation will give information about land anduse necessary direction, and finally the value of production expectations that can be obtained. This study aims to identify the limiting factors for pepper plants in the Galing village, Galing sub-district, Sambas district. To create a class of actual and potential land suitability. This research was conducted in the village of the District Galing Galing Sambas district, then followed by analysis of soil samples in the Laboratory of Chemistry and Soil Fertility Faculty of Agriculture Universitas Tanjungpura. The research started from December 2014 until Fabruari 2015. The results showed that there are two units of Soil Map is Sulfic Endoaquents and Typic Sulfaquents. Actual land suitability on soil type Sulfic Endoaquents (SPT 1) is the appropriate marginal (S2) with inhibitors to Factor pepper plant is a low pH, nutrient availability, and the depth of the actual land sulfidik. Suitability for pepper plants are S3 nfx. While the actual land suitability on the type of Typic Sulfaquents (SPT 2) inhibiting factor is the low pH, nutrient availability, and the depth of the actual land sulfidik. Suitability for pepper plants are N-x. Recommendations for improvements in SPT 1 and SPT 2 is water regulation, liming and fertilizing N, P, and K with the processing level is medium to high, then the suitability of potential land for pepper plants in SPT 1 to be fit while on SPT 2 appropriate to marginal